2021
DOI: 10.1021/acscatal.1c03732
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Kinetic Resolution of Flavonoids via Asymmetric Allylic Alkylation: Construction of Two Contiguous Stereogenic Centers on Nucleophiles

Abstract: The extension of racemization strategies of dynamic kinetic resolution in organic synthesis is a longstanding challenge, especially racemizing two or more stereogenic centers simultaneously. Through the combination of a palladium-catalyzed asymmetric allylic alkylation and a base-promoted retro-oxa-Michael addition, a dynamic kinetic resolution of 2,3-disubstituted flavonoids was achieved with up to 99% enantioselectivities, and two contiguous stereocenters (including a quaternary stereogenic center) were cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Enantioseparation of flavonoids by LC with chiral stationary phases (CSP) started with polysaccharide columns, including cellulose and amylose derivatives, followed by cyclodextrin columns [112,113]. Dynamic kinetic resolution has also been recently described [114].…”
Section: Synthetic Chiral Flavonoids With Antitumor Activitymentioning
confidence: 99%
“…Enantioseparation of flavonoids by LC with chiral stationary phases (CSP) started with polysaccharide columns, including cellulose and amylose derivatives, followed by cyclodextrin columns [112,113]. Dynamic kinetic resolution has also been recently described [114].…”
Section: Synthetic Chiral Flavonoids With Antitumor Activitymentioning
confidence: 99%
“…The asymmetric reaction has been successfully applied to the kinetic resolution (KR) of racemic allylic substrates, yielding substitution products with a high enantiomeric excess (Scheme a). , By contrast, the KR of racemic nucleophiles via EAS remains relatively unexplored . For instance, Hou et al reported the KR of racemic 2,3-dihydro-2-substituted 4-quinolones via enantioselective allylic alkylation, yielding C -allylated products (Scheme b). , In addition, the KR of racemic 2-substituted indolines via enantioselective allylic amination was also investigated, yielding N -allylated products (Scheme c) . However, the resolution of racemic nucleophiles in these examples generally required a stoichiometric base and activated (derivatized) allylic alcohols (e.g., allylic phosphates or allylic carbonates).…”
Section: Introductionmentioning
confidence: 99%
“…Asymmetric (transfer) hydrogenation of multiple substituted ketones has been regarded as a promising method to synthesize functional chiral alcohol derivatives using transition-metal catalysts. , Recently, our group observed that 2,3-disubstituted flavanones are easy to proceed retro-oxa-Michael addition under basic conditions, leading to racemization of two stereocenters simultaneously. Then, a palladium-catalyzed asymmetric allylic alkylation with this strategy was achieved, constructing chiral flavanone derivatives with two contiguous stereocenters (including a quaternary stereogenic center) . Encouraged by this result, we envisioned whether this strategy could be utilized in the asymmetric reduction of flavanoids with a basic catalyst system, which would enable enantioselective synthesis of flavanols with three contiguous stereogenic centers (Scheme ).…”
mentioning
confidence: 99%